Development and psychometric evaluation of performance-based upper extremity motor control test (PB-UE-MCT) for people with cerebral palsy/Desenvolvimento e avaliação psicométrica do Teste de Controle Motor das Extremidades Superiores com Base no Desempenho (PB-UE-MCT) para pessoas com paralisia cerebral - Shams, Fatemeh Etemad; Amini, Malek; Mehraban, Afsoon Hassani; Alizadeh Zarei, Mehdi; Kalani, Dorsa (Cadernos Brasileiros de Terapia Ocupacional, 2021)
Introduction: Upper extremity disorders limits the performance in the activities of daily living, especially, in bilateral (two-handed) activities. Objective: This study was designed to develop a performance-based upper extremity motor control test (PB-UE-MCT) and to measure its psychometric properties (including, convergent validity, intrarater reliability, and interrater reliability) for people with cerebral palsy (CP). Method: The PB-UE-MCT was developed in three phases, including planning, construction, and psychometric evaluation. The participants included 50 people with CP with an age range of 6 to 18 years. To measure internal consistency, Cronbach's alpha was run (n=50). Intrarater and interrater reliability was measured for 25 participants. To assess convergent validity, the correlations of the PB-UE-MCT with the Manual Ability Classification System (MACS) and with the Selective Control Upper Extremity Scale (SCUES) were calculated. Results: The values obtained for Cronbach's alpha (.90 to .96) indicated the excellent internal consistency of the PB-UE-MCT. The ICC values for intrarater reliability and interrater reliability were between .84 and .99 and between .89 and .99, respectively. The correlation coefficients obtained for the items of the PB-UEMCT and those of the MACS were between .51 and .73. The correlation coefficients of the items of the PB-UE-MCT with those of the SCUES were in the range of .67 to .98, which proves the PB-UE-MCT's good to excellent levels of convergent validity. Conclusion: The results confirm that the PB-UE-MCT is a valid and reliable tool for evaluating the upper extremity performance of people with CP through task analysis.